Multiple Encoding in Genetic Editions: The Case of "Faust" - Gerrit Brüning; Katrin Henzel; Dietmar Pravida (Journal of the Text Encoding Initiative)
The aim of the present paper is to show how, and to what extent, the standards of critical genetic editions as applied to Goethe's Faust can be attained within a TEI framework. It proposes and argues for the introduction of two separate transcripts: documentary and textual. Despite the apparent disadvantages of multiple encoding, this approach recommends itself for practical reasons (e.g., avoidance of overlapping hierarchies), and it conveniently reflects the idea that any written document must be considered a material object on the one hand and a medium of textual transmission on the other. In the course of the paper, some aspects and problems of chapter 11 of version 2.0.0 of TEI P5 (the definition and use of the elements and and related issues) will be discussed.